Development of geographical information tools in road realignment for oil palm plantation - Ahmad Daud, Rasydan Ahmad (2019)
Oil palm replanting is essential in improving oil palm production and its cost efficiency. The vital elements in oil palm replanting are optimal agriculture road network and improvement of planting management. The traditional methods and current practices in developing agriculture road are time-consuming especially in a large area. In order to speed up the process, the Least Cost Path Analysis (LCPA) is proposed in this study. The study was carried out in TH Plantation located at Muadzam Shah, Pahang using Interferometric Synthetic Aperture Radar (IfSAR) data. Digital elevation models (DEMs) developed from IfSAR data is used to generate a slope map. By combining both of the slope factor and elevation factor, a Least Cost Path Analysis can be generated in order to find the optimal agriculture road network conditions. Sensitivity analysis is used to determine the percentage of influence in a Weighted Overlay tool. A model builder in ArcGIS collaborated with python language are then used to generate an automated system for producing optimal agriculture road network at the oil palm replanting area. Models developed in this context are workflows that chain together sequences of geoprocessing tools to automate the optimal agriculture road network management system. ArcGIS Python Add-In Wizard is used to develop tools that will be added in the existing standard ArcGIS tools and will be geospatial tools for oil palm plantation. In this study, the percentage of influence was assessed and determined before being used for the Weighted Overlay tool. It was tested using sensitivity analysis. Using this technique, 9 sets of data were tested. These data were compared and analysed into several criteria such as maximum elevation, maximum slope, length of the road, labour costing, time costing, and fuel costing. The result indicates that 60% slope and 40% elevation was good enough to be used as the Weighted Overlay tool percentage of influence. An LCPA tool was developed to be used as an extension tool in ArcMAP 10.3. The tool has been successfully developed and tested in ArcMAP 10.3 software. This tool allows the user to develop a proposed agriculture road. When the tool was completed, T-test analysis was done to evaluate the effectiveness of the developed tool using several sets of the road network.